1997
DOI: 10.1002/lt.500030507
|View full text |Cite
|
Sign up to set email alerts
|

Orthotopic liver transplantation with preservation of portocaval flow compared with venovenous bypass

Abstract: Conventional liver transplantation requires crossclamping of the hepatic pedicle and inferior vena cava, leading to severe hemodynamic and metabolic disturbances, usually attenuated by the use of venovenous bypass. A more recent surgical technique, piggyback with temporary portocaval shunting, preserves both caval and portal blood flows. The aim of this study was to compare the two methods prospectively. Forty-four patients with chronic liver disease were studied. Local anatomic conditions guided the surgeon t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 18 publications
2
10
0
Order By: Relevance
“…In 1993, Tzakis et al [15], and afterwards Belghiti et al in 1995 [16, 17], described the use of temporary portocaval shunt in OLT. It has already been demonstrated that the use of temporary portocaval shunt associated with the preservation of the inferior vena cava can be performed safely in most patients, without the need for veno‐venous bypass, and with haemodynamic and renal improvements (Table 1) [18, 19]. We could indeed confirm this fact with a prospective randomised study that demonstrated that the association of a temporary portocaval shunt with the preservation of the inferior vena cava technique achieved better haemodynamic stability during the anhepatic phase, and this was associated with lower blood transfusion requirements and better renal function, mainly in those patients with higher portal blood flow or higher portocaval gradient [20].…”
Section: Native Liver Removalsupporting
confidence: 55%
“…In 1993, Tzakis et al [15], and afterwards Belghiti et al in 1995 [16, 17], described the use of temporary portocaval shunt in OLT. It has already been demonstrated that the use of temporary portocaval shunt associated with the preservation of the inferior vena cava can be performed safely in most patients, without the need for veno‐venous bypass, and with haemodynamic and renal improvements (Table 1) [18, 19]. We could indeed confirm this fact with a prospective randomised study that demonstrated that the association of a temporary portocaval shunt with the preservation of the inferior vena cava technique achieved better haemodynamic stability during the anhepatic phase, and this was associated with lower blood transfusion requirements and better renal function, mainly in those patients with higher portal blood flow or higher portocaval gradient [20].…”
Section: Native Liver Removalsupporting
confidence: 55%
“…Although the MPB technique decreases the risk of outflow obstruction in comparison with PB,24, 16 some investigators have proposed that this modification might not be the best choice in a percentage of recipients. An enlarged caudate lobe or voluminous donor graft,18, 17, 10 anatomic limitations and abnormalities of the IVC,18, 19 and adhesions between the liver and the retrohepatic IVC as well as the caudate lobe in some chronic inflammatory states10, 20 are situations that limit the use of caval‐preserving techniques. Belghiti et al24 showed that difficult hepatic dissection of a large liver, injury to the IVC, injury to hepatic veins or outflow obstruction after graft reperfusion due to graft rotation, and anastomotic stricture or compression can be managed by temporary IVC clamping 24.…”
Section: Discussionmentioning
confidence: 99%
“…The PB technique has several advantages over conventional LTx, such as avoiding the use of VVB and suprahepatic and infrahepatic IVC anastomosis; this leads to shortening of the total operative time and warm ischemia time,16–18, 20–28 a reduction in complications specific to VVB,18, 21, 23, 28–32 and fewer complications associated with dissection of the retrohepatic IVC, such as phrenic nerve injuries and hemorrhagic complications 16, 18, 23, 30, 33, 34. In addition, the PB technique allows an improvement of intraoperative cardiac and hemodynamic stability by maintenance of venous return,19, 24–27 a reduction in intraoperative blood and fluid transfusion,25, 26, 35, 36 improved postoperative renal function,17, 24, 26, 27 better maintenance of oxygen delivery to tissue throughout surgery,19 and a reduction in ICU and hospital stay 17, 25, 26…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, many centres currently using PC‐LT technique consider VVB redundant. The potential problem of occlusion of splanchnic flow without VVB can be overcome by creating a temporary portocaval shunt (TPCS) to maintain portal flow [6,10]. Consequently the PC‐LT has become increasingly popular among liver transplantation centres all over the world.…”
Section: Introductionmentioning
confidence: 99%